Relevance of Protein Isoforms in Proteomic Studies - de la Cadena, Maria P.; Rodriguez-Pineiro, Ana M.; Alvarez-Chaver, Paula; Martinez-Zorzano, Vicenta S.; Rodriguez-Berrocal, Francisco J. (Current Proteomics, 2007)
The development of proteomics has generated considerable interest in the search of new biomarkers since proteins reflect biological conditions more directly than nucleic acids. However, despite the large number of laboratories reporting exciting and successful studies within this frame, we have not witnessed its clinical application yet. One of the reasons for this failure is the difficult validation of the results extracted from differential protein expression studies, mainly because the numerous pre- and post-translational events lead to the appearance of the so-called isoforms, which the immunochemical methods employed fail to distinguish due to a lack of isoform-specific antibodies. Though the term “isoform” does not exist as such according to the IUPAC, with the development of proteomics this denomination is used to refer to various forms of a protein which charge or mass properties produce different mobility in two-dimensional gels, irrespectively of their genetic origin. In this review, we address this issue and consider the different definitions of “isoforms”; we also explain the origins of the protein diversity, from the early mechanisms of RNA editing and alternative splicing to the different types of post-translational modifications. From the research point of view, we address the utility of the proteomic methods that allow isoform detection and distinction, as well as the issue of isoform annotation in databases. From an applied point of view, we consider the problem isoforms involve in the clinical practice, together with their relevance in the disease biomarker field and their role during validation. Lastly, we provide some examples of well-known proteins for which isoforms have been reported in literature.
Keywords: cancer